Lord of the flies - Golding, William, 1911-1993. (New York : Penguin Books, 1954)
Few works in literature have received as much popular and critical attention as Nobel Laureate William Golding's Lord of the Flies. Since its publication in 1954, it has amassed a cult following, and has significantly contributed to our dystopian vision of the post-war era. When responding to the novel's dazzling power of intellectual insight, scholars and critics often invoke the works of Shakespeare, Freud, Rousseau, Sartre, Orwell, and Conrad. Golding's aim to "trace the defect of society back to the defect of human nature" is elegantly pursued in this gripping adventure tale about a group of British schoolboys marooned on a tropical island. Alone in a world of uncharted possibilities, devoid of adult supervision or rules, the boys attempt to forge their own society, failing, however, in the face of terror, sin, and evil. Part parable, allegory, myth, parody, political treatise, and apocalyptic vision, Lord of the Flies is perhaps the most memorable tale about "the end of innocence, the darkness of man's heart."
Keywords: Shipwreck survival -- Fiction; Castaways -- Fiction; Islands -- Fiction; Boys -- Fiction; Interpersonal relations -- Fiction; Adventure fiction